ส่วนประสมการตลาดที่มีผลต่อผู้หญิงในอำเภอเมืองลำปางในการซื้อผลิตภัณฑ์ต้านริ้วรอยบนใบหน้า - โชติรส หอเจริญ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2017)
The objective of this independent study was to study marketing mix factors that affected women in Mueang Lampang District towards buying anti-agin facial products. The data was collected by questionnaire distributed to 400 women, 25-60 years old, living in Mueang Lampang District who had bought anti-aging facial products. The data was then analysed using descriptive statistics namely frequency, percentage and mean. F-test (One-way ANOVA) was used to analyse the differences in the questionnaire respondents’ general information, which were age, education and career towards marketing mix. Independent Sample T-test was used to analyse the differences in the respondents’ buying behaviour (type of anti-aging facial product) towards marketing mix. The results of the study showed that most questionnaire respondents were 25-29 years old, single, with Bachelor’s degree. They were government officials or state enterprise employees, with monthly income of 10,000-20,000 baht. The study of their buying behaviour showed that the respondents bought Olay the most. They bought the product at cosmetic counters in department stores. They bought the product when they almost ran out of it and bought the product 2-3 times a month. They spent 1,000-2,000 baht per purchase. They made decision to buy themselves and the reason for buying was to prevent wrinkles. They knew about the product from acquaintances. The study of marketing mix showed that the respondents ranked the overall marketing mix at the high level, in the following order: marketing promotion, product, price, and place. For each category, the highest ranked sub-factors were as follows. For product, the product was allergy-free. For price, the price matched the quality. For marketing promotion, information about the product and the service by salespeople were given. For place, it was convenient to buy the product. For problems in buying anti-aging facial products, the respondents said the price was too high for the quality and the quantity of the product.